IMPLEMENTASI AKAD ISTISHNA’ PADA JUAL BELI RUMAH PERSPEKTIF FATWA MUI NO.06/DSN-MUI/IV/2000 : Studi Kasus di PT. Azzura Griya Utama Bekasi - Asroni; Irvan Iswandi (Melati Institute, 2022)
Azzura Griya Utama Bekasi is a company engaged in property, namely buying and selling houses using a pure sharia system, the manufacturing process will wait for an order and will be made according to the buyer's request. The payment process is allowed buyers to make payments in advance, in the middle, or at the end of the transaction without a specified time limit. This study has two formulations of the problem that will be studied, namely how to implement the istishna’ contract in buying and selling houses at PT. Azzura Griya Utama Bekasi, and how is the review of the istishna' contract No.06/DSN-MUI/IV/2000 on the implementation of the istishna' contract in the sale and purchase of houses at PT. Azzura Griya Utama Bekasi. This research is classified as research that directly comes to the field to conduct research. This study used a descriptive analysis approach. In terms of data collection techniques, this study used interviews and documentation with informants. In addition, for data processing, the researchers used qualitative methods. In this study, two conclusions were obtained. First, the implementation of istishna' contract in the sale and purchase of houses at PT. Azzura Griya Utama Bekasi is in accordance with the study of the istishna’ contract theory, namely the provisions of the goods ordered are clear in form, quantity, and information. For the method of payment, it is in accordance with the istishna’ contract, namely, it is permissible to pay upfront, in the middle, or at the end of the transaction when the goods ordered are ready to be received by the buyer. The unspecified payment period is in accordance with the istishna’ contract where there is no time limit and no interest that contains elements of usury. Second, regarding the practice of istishna' contract that exists at PT. Azzura Griya Utama Bekasi, the theory used is in accordance with the provisions regarding payment and provisions regarding goods made that are in line with the practice of istishna' contract as described from the Fatwa MUI of DSN-MUI No.06/IV/2000.